Infectious Morbidity in Closed Long-Term Care Facilities in the «Pre-COVID Stage» - V. G. Akimkin; N. G. Davydova; S. V. Ugleva; Zh. B. Ponezheva; S. V. Shabalina (Эпидемиология и вакцинопрофилактика, 2023)
Relevance. Elderly people have become the fastest growing segment of the global population over the past few decades. The number of people over the working age in Russia, and with them citizens living in closed long-term care facilities (CLTFS), is growing. Residents of these organizations belong to the risk group, and CLTFS have a number of characteristics that turn these institutions into a unique environment for the spread of infectious diseases.Aims. To analyze the CLTFS residents infectious morbidity in the "pre-covid stage" (according to literature sources). A scientific review of research in Russian and English using information portals and platforms has been carried out eLIBRARY. ru , Web of Science, PubMed, Google Academy and Scopus for the period 1981-2022. The search was carried out by keywords. Information about the most frequent infectious diseases affecting residents of closed long-term care institutions was the criterion for inclusion in the sample of publications. Out of 16171 initially identified articles, 61 publications were selected after initial analysis.Conclusions. According to various estimates, the leading infectious diseases in CLTFS were: acute respiratory infections, pneumonia, urinary tract infections, skin and mucous infections, acute intestinal infections. The article describes pathogens and their prevalence in CLTFS including pathogens with multiple drug resistance (MDR), describes the resistance of bacteria to antimicrobial drugs formation problem in these organizations, as well as development of certain diseases risk factors. Studies conducted in various CLTFS in Europe, Russia, the USA, and Asia indicate a high prevalence of infectious diseases among their residents, high colonization of residents with antimicrobial-resistant pathogens, as well as the infection transmission probability from the CLTFS and its spread to other long-term care institutions and medical and preventive organizations.